High-Dose Cyclophosphamide Administration Orchestrates Phenotypic and Functional Alterations of Immature Dendritic Cells and Regulates Th Cell Polarization - Bao, Lei; Hao, Changfu; Wang, Juan; Wang, Di; Zhao, Youliang; Li, Yiping; Yao, Wu (Frontiers in Pharmacology, 2020)
High-dose cyclophosphamide (CTX) inhibits the immune response. Dendritic cells (DCs) are professional antigen presenting cells (APCs) with a crucial role in initiating immune responses and sustaining immune tolerance. The relative contribution of DCs to immunosuppression induced by high-dose CTX is not well-documented. In this study, we employed the CTX-induced immunosuppressive rat model to examine alterations in DCs. We generated and cultured monocyte-derived immature DCs (imDCs) in vitro and explored their capacity of antigen uptake, T cell priming, cytokine production, and surface marker expression following high-dose CTX. Subsequently, we co-cultured CTX-treated imDCs with Th cells to determine Th cell polarization, and further explored the Toll-like receptor/Myeloid differentiation primary response 88/Mitogen-activated protein kinase (TLR/MyD88/MAPK) pathway. Our results show reduced cell number and surface maker alterations were in splenic CD103+ DCs of CTX-treated immunosuppressed rats. In vitro, high-dose CTX weakened the antigen uptake capacity and enhanced the T cell priming capacity of imDCs, in addition to triggering imDC surface marker alterations. TLR, MyD88, and MAPK expression levels, involved in mediating Th cell polarization, were also significantly elevated. Our collective findings indicate that high-dose CTX administration potentiates phenotypic and functional alterations of imDC. Such changes may contribute to the regulation of Th polarization.